2022
DOI: 10.1128/jb.00615-21
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Antagonizes Pseudomonas aeruginosa Growth in Mixed-Species Interactions

Abstract: Many infections are polymicrobial and biofilm-associated in nature. Iron is essential for many metabolic processes and plays an important role in controlling infections, where the host restricts iron as a defense mechanism against invading pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…However, Tan et al . found that E. faecalis can lower the environmental pH by exporting lactic acid to antagonize P. aeruginosa growth within biofilms under iron-restricted conditions [ 41 ].…”
Section: Pathogenic Properties Of E Faecalis Assoc...mentioning
confidence: 99%
“…However, Tan et al . found that E. faecalis can lower the environmental pH by exporting lactic acid to antagonize P. aeruginosa growth within biofilms under iron-restricted conditions [ 41 ].…”
Section: Pathogenic Properties Of E Faecalis Assoc...mentioning
confidence: 99%
“…Studies have shown that drug efflux pumps were differentially expressed upon the co-culture of P. aeruginosa with streptococcal flora [ 122 ], with a role for quorum sensing and AI-2 signaling proposed. A role for the MexAB-OprM efflux pump has been proposed in growth antagonism of P. aeruginosa by Enterococcus faecalis , though the NalC-iron related mechanism of this modulation remains to be fully determined [ 123 ]. The recent finding that utilization of secondary metabolites produced by co-colonizing competitors underpins bacterial dominance suggests that efflux systems and metabolic flux will play an important role in shaping the dynamics of these communities [ 124 ].…”
Section: Efflux Pumps and Polymicrobial Communitiesmentioning
confidence: 99%
“…Interestingly, this synergistic relationship tends to be reversed under iron starvation. It has been shown that E. faecalis inhibits P. aeruginosa growth in mixed species biofilm culture in iron‐depleted environment (Tan et al., 2022). This inhibition is attributed to the upregulation of ldh1 in E. faecalis , which encodes the production of l ‐lactate dehydrogenase (Keogh et al., 2018).…”
Section: Ironmentioning
confidence: 99%